Spycraft - Wallace, Robert; Schlesinger, Henry R.; Melton, H. Keith
Tells the amazing life and death stories about this little-known group, much of which has never before been revealed. Against the backdrop of some of the most critical international events of recent years the authors show the real technical and human story of how the CIA carried out its most secret missions.